Hot Maid Cleaning Services / Nurul Shafikah Abd Rahman ... [et al.] - Abd Rahman, Nurul Shafikah (2013)
Hot Maids Cleaning Services (HMCS) is a residential cleaning service serving upper class services for household, office in cleanly. Through generous human capital investment HMCS will exceed our customer's expectation. household or officer which are not have time to clean their house or office will find us and we will give our services to them. These targeted people or family are willing to pay premium for the service because of the high level of professionalism and trustworthiness that is offered. This target market will focused on because of their steady reliance on cleaning services that we offered to them to keep their home clean. Hot maid Cleaning Services is a business to provide our clients with reliable, quality based cleaning service. We also represent the best value for money as well as ensuring that our clients' needs and expectation are not only attend but also exceeded. We aim to provide hygienic, high performing facilities for our customers with minimal impact on our ecosystem.